PERAN MEDIA KOMUNITAS DALAM PENDIDIKAN BUDAYA LITERASI DI INDONESIA. STUDI KASUS TABLOID KORAN2AN SLANK - Lasawedy, Aslamuddin (CV Widina Media Utama, 2026)
Print media play a strategic role in shaping popular cultural literacy practices amid the development of the media industry and popular music in Indonesia. One notable example of print media is Koran2an Slank or Koran Slank, a print publication that emerged from the Indonesian rock band Slank. This study aims to analyze the role of Koran2an Slank as a print media platform in fostering popular cultural literacy in Indonesia. The research employs a descriptive qualitative approach using a literature review method. Data were collected from articles, books, and scholarly works related to cultural literacy, media literacy, and music journalism. The findings indicate that Koran2an Slank functions not only as a community information medium but also as a space for meaning-making, collective identity expression, and a vehicle for politic and cultural literacy education among its readers and the Slankers community. The publication presents alternative narratives outside mainstream media and strengthens participatory music literacy practices. In conclusion, Koran2an Slank represents a model of community media that contributes to strengthening popular cultural literacy and fostering social politics awareness within the sphere of Indonesian popular culture.ABSTRAKMedia cetak memiliki peran strategis dalam membentuk praktik budaya literasi di tengah perkembangan industri media dan musik populer di Indonesia. Salah satu media cetak yang menarik untuk dikaji adalah tabloid bulanan Koran2an Slank atau Koran Slank. Sebuah media cetak yang lahir dari rahim Slank, salah satu supergrup musik Indonesia. Penelitian ini bertujuan untuk menganalisis peran Koran2an Slank sebagai media komunitas dalam pendidikan budaya literasi di Indonesia. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kepustakaan. Data diperoleh dari artikel, buku, dan kajian terkait budaya literasi, literasi media, serta jurnalisme musik. Hasil penelitian menunjukkan bahwa Koran2an Slank atau Koran Slank tidak hanya berfungsi sebagai media informasi dan ekspresi identitas komunitas, pun juga menjadi ruang produksi gagasan perlawanan politik dan budaya melalui musik, serta medium pendidikan budaya literasi di kalangan pembaca dan komunitas Slankers. Media ini menghadirkan narasi alternatif di luar media arus utama dan memperkuat praktik literasi musik yang partisipatif. Kesimpulannya, Koran2an Slank merepresentasikan model media cetak yang berkontribusi terhadap penguatan budaya literasi dan pembentukan kesadaran sosial politik dalam ruang budaya populer Indonesia.